1997
DOI: 10.1111/j.1365-2621.1997.tb15441.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxymyoglobin Oxidation as Affected by Oxidation Products of Phosphatidylcholine Liposomes

Abstract: Supernatants (105,000 ϫ g) of oxidized phosphatidylcholine (PC) liposomes contained higher levels of thiobarbituric acid-reactive substances, and caused greater metmyoglobin formation when combined with oxymyoglobin than those of controls (C) or PC plus tocopherol (PCT) (PϽ0.05). Products of PC liposome oxidation crossed dialysis membranes (mol wt cut-off ϭ 500 Dalton) and accelerated the oxidation of oxymyoglobin more than C or PCT (PϽ0.05). The addition of known oxidation products of oleic acid and linoleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 21 publications
1
33
1
2
Order By: Relevance
“…Many authors have defended this hypothesis. 30,52,53 However, the fact that rosemary extract inhibited both lipid and myoglobin oxidation whereas borage meal and green tea extract strongly inhibited lipid oxidation but not metmyoglobin formation suggests that the mechanisms involved are independent of each other. The complex effects of NaCl reported in experiment 1, which enhanced lipid oxidation but prevented colour loss, strengthen this view.…”
Section: Colourmentioning
confidence: 90%
“…Many authors have defended this hypothesis. 30,52,53 However, the fact that rosemary extract inhibited both lipid and myoglobin oxidation whereas borage meal and green tea extract strongly inhibited lipid oxidation but not metmyoglobin formation suggests that the mechanisms involved are independent of each other. The complex effects of NaCl reported in experiment 1, which enhanced lipid oxidation but prevented colour loss, strengthen this view.…”
Section: Colourmentioning
confidence: 90%
“…Chan et al (1997) reported a prooxidative effect of oxymyoglobin in liposome systems. The lipid oxidation in fish muscle was promoted by the oxidation of myoglobin, which played a considerable role in the generation of hydroperoxides (Sohn et al, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Lipid oxidation is a chain reaction consisting of initiation, propagation, and termination reactions. This phenomenon can be influenced by both intrinsic and extrinsic factors such as the fatty acid composition, the concentration of pro-oxidants, endogenous ferrous iron, heme proteins, enzymes, pH, temperature, ionic strength and oxygen consumption (Chan, Faustman, & Decker, 1997;Grunwald & Richards, 2006;Nawar, 1996;Sohn et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the decrease in redness (a* values) and the increase in hue values (H*) appear to be suitable descriptors of meat color deterioration occurring over time; these descriptors impart a less-intense red color and a worse appearance of the meat (Nieto et al, 2010). The variation of these descriptors and of hue values in particular have been proved to be highly associated with the accumulation of metmyoglobin on meat surface (Luciano et al, 2011), as a consequence of the increased oxidation of oxymyoglobin to metmyoglobin (Chan et al, 1997). The meat samples of the two dietary treatments (Table 2) showed that redness decreased (P = 0.046) and hue values increased (P = 0.036).…”
Section: In Vitam Performance Traitsmentioning
confidence: 99%